Examining the Impact of the Solo-Yogyakarta Toll Road Construction on Farmers’ Assets and Psychological Well-being - Bekti Wahyu Utami; Sunarru Samsi Hariadi; Alia Bihrajihant Raya (Universitas Sebelas Maret, 2024)
This study investigates the psychological impact of farmers’ sentiments on land conversion associated with the national strategic project for constructing the Solo-Yogyakarta toll road, focusing on the asset aspects of farmers’ families. Employing descriptive and survey approaches, supplemented by in-depth interviews to enhance the research design, the study utilized a random sampling method with a proportional cluster, encompassing a sample size of 258 participants. Data collection was conducted through questionnaires, and analysis involved cross-tabulation and chi-square descriptive analysis to examine relationships between factors. The findings reveal that farmers experience psychological distress, particularly sadness, due to the change in land use and the option to sell their land. Farmers’ attitudes toward compensation procedures were generally neutral. Overall, the study highlights the significant psychological impact of land conversion, predominantly manifesting as sadness among farmers. The research underscores the need for policy development to establish support programs by relevant entities, ensuring that compensation funds are effectively utilized to generate new income sources for the affected farmers.